2020
DOI: 10.1152/jn.00064.2020
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the ipsilateral motor network in unilateral voluntary muscle contraction: the cross-activation phenomenon

Abstract: Voluntary force production requires that the brain produces and transmits a motor command to the muscles. It is widely acknowledged that motor commands are executed from the primary motor cortex (M1) located in the contralateral hemisphere. However, involvement of M1 located in the ipsilateral hemisphere during moderate to high levels of unilateral muscle contractions (>30% of the maximum) has been disclosed in recent years. This phenomenon has been termed cross-activation. The activation of the ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
2
15
0
Order By: Relevance
“…A similar finding was found in a previous study using a visuomotor tracking task, where smaller pre-training beta activity over the ipsilateral cortex was related to better performance after practice (Espenhahn et al, 2019). Although the functional role of the ipsilateral cortex in motor control and learning is still under debate (Uehara and Funase, 2014;Barany et al, 2020;Cabibel et al, 2020), these results are consistent with the view that a more lateralized activity pattern is beneficial for motor performance (Takeuchi et al, 2012).…”
Section: Practice-related Changes In Task-related Power Are Dependentsupporting
confidence: 89%
“…A similar finding was found in a previous study using a visuomotor tracking task, where smaller pre-training beta activity over the ipsilateral cortex was related to better performance after practice (Espenhahn et al, 2019). Although the functional role of the ipsilateral cortex in motor control and learning is still under debate (Uehara and Funase, 2014;Barany et al, 2020;Cabibel et al, 2020), these results are consistent with the view that a more lateralized activity pattern is beneficial for motor performance (Takeuchi et al, 2012).…”
Section: Practice-related Changes In Task-related Power Are Dependentsupporting
confidence: 89%
“…Finally, it has also been demonstrated that cooperation between the two motor cortices during skill learning harnesses plasticity in the ipsilateral hemisphere improving motor learning [30]. Taken together, this evidence supports the idea that the ipsilateral M1 activation plays a crucial role in the control of unilateral hand movements [18,19]. It should be underlined that the activation of the two motor cortices during unilateral hand movements is not the same.…”
Section: Introductionsupporting
confidence: 67%
“…It has been well established that unimanual arm movements elicit bilateral activity in the sensorimotor areas [18,19]. However, the meaning of ipsilateral hemisphere signals is considerably debated.…”
Section: The Left Hemisphere Role's In Actions Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…10-19 These changes within the contralesional cortex could contribute directly to recovery. For example, in humans, both hemispheres are recruited during execution or learning of unilateral motor tasks, 44-46 suggesting both motor cortices may work cooperatively during motor learning. 47 In people with stroke, increased activation of the contralesional cortex on imaging is reported during paretic upper limb movement, 48,49 while suppression of contralesional activity has been shown to impair motor performance.…”
Section: Discussionmentioning
confidence: 99%